2015
DOI: 10.1097/fjc.0000000000000259
|View full text |Cite
|
Sign up to set email alerts
|

Antiarrhythmic Mechanisms of SK Channel Inhibition in the Rat Atrium

Abstract: SK channel inhibition modulates multiple parameters of AP. It prolongs the AP duration and shifts the RMP towards more depolarized potentials through direct ISK block. This indirectly leads to sodium channel inhibition through accumulation of state dependently inactivated channels, which ultimately slows conduction and decreases excitability. However, a contribution from a direct sodium channel inhibition cannot be ruled. We here propose that the primary antiarrhythmic mechanism of SK channel inhibition is thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 34 publications
(43 reference statements)
4
30
0
Order By: Relevance
“…More recent models of re-entry predict that changes, which prolong or cause heterogeneous ERP, do indeed increase source-to-sink mismatch in excitation, in this way slowing conduction velocity. As we recently reported [25], slowing of CV was mirrored by reversed changes in ERP, opposing wavelength shortening by actually prolonging the theoretical spatial wavelength. This concept could explain the relatively high efficiency of sodium channel blockers in the abolishment of re-entrant arrhythmias.…”
Section: Refractoriness and Conduction Velocity In Re-entrysupporting
confidence: 64%
See 1 more Smart Citation
“…More recent models of re-entry predict that changes, which prolong or cause heterogeneous ERP, do indeed increase source-to-sink mismatch in excitation, in this way slowing conduction velocity. As we recently reported [25], slowing of CV was mirrored by reversed changes in ERP, opposing wavelength shortening by actually prolonging the theoretical spatial wavelength. This concept could explain the relatively high efficiency of sodium channel blockers in the abolishment of re-entrant arrhythmias.…”
Section: Refractoriness and Conduction Velocity In Re-entrysupporting
confidence: 64%
“…A clear relationship between refractory period, conduction velocity and functional wavelength exists [25]. According to the classical leading-circle theory [26], these two electrophysiological parameters are considered independent factors (WL = CV x ERP).…”
Section: Refractoriness and Conduction Velocity In Re-entrymentioning
confidence: 99%
“…In addition to Na v 1.5 and K ir 2.1, previous studies have reported preferential localization of K V 1.5,(19) the voltage-gated, shaker-related potassium channel, small conductance calcium-activated potassium (SK) channels(26), and K ir 6.2, the ATP-sensitive potassium channel,(9) at the intercalated disc. Also, we have demonstrated that activation of the rapid (HERG)(14) and slow (KvLQT1)(33) delayed rectifier potassium channels as well as K ir 6.2 can modulate cardiac conduction.…”
Section: Discussionmentioning
confidence: 99%
“…80 NS8593 as well as several small molecule blockers of K Ca 2 channels have shown efficacy in protecting against and terminating atrial fibrillation both ex vivo and in vivo across a number of different species. 81 Intriguingly, this concept also appears to be viable after hypertension induced cardiac remodeling.…”
Section: Negative Modulation Of K Ca 2 Channelsmentioning
confidence: 99%